Miniaturization of dual bands fractal-based microstrip patch fractal antenna for X and Ku bands applications - Froumsia, Dokrom; Jean-Francois, Essiben Dikoundou; Houwe, Alphonse; Kolyang; İnç, Mustafa (Springer Heidelberg, 2022)
In this work, the process of fractal-based rectangular microstrip patch antenna miniaturization was described. The principle was to start from a conventional microstrip patch antenna of size 8.13 x 5 mm2 resonating at 11.71 and 16.84 GHz with - 12.09 and - 21.5 dB as reflection coefficients respectively, suitable for X and Ku bands application. Sierpinski Carpet's approach was implemented up to the third iteration on the conventional rectangular patch antenna. The design and simulation were carried out using CADFEKO 7.0 software. The results of the proposed model show well-optimized characteristics for both resonant frequencies: 11.16 and 17.16 GHz with - 30 and - 29.93 dB as reflection coefficient respectively and better bandwidth enhancing from 2.87 GHz for the conventional microstrip to 3.20 GHz for the proposed fractal antenna. The value of all antenna parameters such as VSWR, gain, radiation pattern, Smith chart, Bandwidth, current distribution is an acceptable range. The size of the model obtained in the third iteration could be reduced to about 67% of the size of the conventional rectangular patch antenna.